Impact of prooxidant-antioxidant imbalance on the biological age and the rate of aging in arterial hypertension with type 2 diabetes mellitus - Nemtsova, V. D. (Запорізький державний медико-фармацевтичний університет, 2020)
Purpose:to study the state of oxidative-antioxidative balance and its influence on the biological age (BA) and the features of aging in patients with a comorbid course of arterial hypertension (AH) and type 2 diabetes mellitus (T2DM). Materials and methods.In 96 patients with II stage AH and T2DM and 40 patients with isolated II stage AH (IAH), a BA, rate of aging (according to the method of V. P. Voytenko et al.) and oxidative stress (OS) indexes (activity of glutathione peroxidase, serum levels of sulfhydryl groups, malonic dialdehyde, 8-hydroxy-2-deoxyguanosine) were investigated. Results. In IAH patients, physiological aging (PhA) was detected in 12.5 %, delayed type of aging (DTA) – in 55.0 %, accelerated type of aging (ATA) – in 32.5 %. In AH and T2DM, PhA was in 9.4 %, DTA – in 31.3 %, ATA – in 59.4 % of patients. Only 5 patients (12.5 %) with IAH and 3 patients (3.13 %) with AH and T2DM had no signs of OS. The patients with ATA in comorbid pathology were characterized by a significant activation of oxidative and stimulation of antioxidant systems compared to those with DTA, which was less common among IAH patients. The presence of correlations between the antioxidant system indicators and age parameters characterizing the degree of aging was found. Conclusions. OS, which is one of the significant factors resulting in premature aging, was more enhanced in AH and T2DM than in IAH. OS manifestations were more significant in ATA regardless of nosology, but were more pronounced in AH and T2DM. Therefore, OS evaluation together with age-related characteristics can be used both to assess an organism state and as an integral indicator characterizing the effectiveness of therapeutic and preventive measures.

Мета роботи – вивчити стан оксидантно-антиоксидантного балансу та його вплив на біологічний вік (БВ) та особливості старіння у хворих на артеріальну гіпертензію (АГ) із супутнім перебігом цукрового діабету 2 типу (ЦД2Т). Матеріали та методи. У 96 пацієнтів з АГ ІІ ступеня та ЦД2Т і 40 пацієнтів з ізольованою АГ (ІАГ) ІІ ступеня досліджували біологічний вік, темпи старіння (за методом В. П. Войтенка та співавт.) і показники оксидативного стресу (ОС): активність глутатіонпероксидази, рівні сульфгідрильних груп, малонового діальдегіду, 8-гідрокси-2-деоксигуанозину в сироватці крові. Результати. При ІАГ фізіологічне старіння (ФС) виявили у 12,5 % пацієнтів, уповільнений тип старіння (УТС) – у 55,0 %, прискорений тип старіння (ПТС) – у 32,5 %. При АГ та ЦД2Т: ФС – у 9,4 %, УТС – у 31,3 %, ПТС – у 59,4 % хворих. Тільки в 5 (12,5 %) пацієнтів з ІАГ і 3 (3,13 %) пацієнтів з АГ і ЦД2Т не виявили ознаки ОС. Наявність ПТС при коморбідній патології характеризувалась вірогідною активацією оксидантної та стимуляцією антиоксидантної системи порівняно з особами з УТС, що не так характерно для пацієнтів з ІАГ. Встановили кореляційні зв’язки між показниками антиоксидантної системи й віковими показниками, що характеризують ступінь старіння. Висновки. Оксидативний стрес, який є одним зі значущих чинників, що призводять до передчасного старіння, при АГ і ЦД2Т був вираженішим, ніж при ІАГ. Прояви ОС були значущі при ПТС незалежно від нозології, але при АГ і ЦД2Т вира-жені більше. Тому дослідження оксидативного стресу разом із віковими характеристиками можна використовувати і для оцінювання стану організму, і як інтегральний показник, що характеризує ефективність лікувально-профілактичних заходів.
Вплив прооксидантно-антиоксидантного дисбалансу на біологічний вік і темпи старіння при артеріальній гіпертензії та цукровому діабеті 2 типу
Keywords: hypertension; type 2 diabetes mellitus; aging; oxidative stress; артеріальна гіпертензія; цукровий діабет 2 типу; старіння; оксидативний стрес